Sufism in Western contexts - Hermansen, Marcia K. 1951-; Zarrabi-Zadeh, Saeed (Brill, 2023)
"Sufism in Western Contexts explores both historical trajectories and multiple contemporary manifestations of Islamic mystical movements, ideas, and practices in diverse European, North and South American countries, as well as in Australia-all traditionally non-Muslim regions of the "global West". From early French and British colonial administrators who admired Persian poetry to nineteenth century American transcendentalists onto today's female whirling dervishes and South Asian and Middle Eastern immigrant Sufi guides and their movements, the many faceted expressions of Sufism such as its role in Western esotericism and its new articulations in cyberspace are traced and analyzed by international experts in the field"--
Keywords: Geschichte; Sufismus; Gesellschaft; Islam; Sufism / Europe / History; Sufism / Foreign countries / History; Sufism / Western countries / History; Sufism / North America / History; Sufism / Latin America / History